Efektivitas Saringan Keramik sebagai Media Filtrasi untuk Menurunkan Kadar Besi (Fe) pada Air Sumur Bor: (Studi Kasus di Desa Basule Kecamatan Lasolo) - Talib, Fiklin Yauri; Ndibale, Wa; Adami, Aryani (Universitas Muhammadiyah Kendari, 2025)
Bore well water in Basule Village, Lasolo District, contains iron (Fe) levels exceeding the established quality standards, potentially posing negative impacts on health and the environment. This study aims to evaluate the effectiveness of ceramic filters made from clay and rice husk in reducing iron levels in bore well water. The research method used is a laboratory experiment, with water samples taken from three bore wells. The ceramic filter was made using a composition of 80% clay and 20% rice husk, then fired at ±850°C to create micro-pores as a filtration medium. The bore well water was tested before and after filtration using the atomic absorption spectrophotometry (AAS) method to measure iron levels. The results showed that the ceramic filter significantly reduced iron levels. The average iron reduction effectiveness reached 84.88%, with the highest reduction of 96.67% in wells with initially higher Fe concentrations. Thus, ceramic filters made from clay and rice husk have proven effective in improving bore well water quality and can serve as a simple and eco-friendly alternative for clean water treatment.